2007
DOI: 10.1111/j.1750-3841.2007.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite‐Radical Anions in Isolated Soy Proteins

Abstract: Aqueous mixtures of manganese and sulfite, at levels found in isolated soy proteins (ISP) and defatted soy flakes, spontaneously react in the presence of oxygen to produce methanethiol from the 1-electron oxidation of methionine. The carbon and sulfur of methanethiol originate from the methyl-carbon and sulfur of methionine. Similar aqueous mixtures of sulfite, manganese, and oxygen also produce sufficient levels of free radicals to degrade fluorescein. The degradation of methionine by free radicals generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Broad peaks are typical of overlapping signals in polycrystalline or powdered samples. All of the reducing agents examined here have been shown to catalyze the oxidation of methionine and/or linoleic acid when added to ISP aqueous slurries (Boatright and Lu 2007; Lei and Boatright 2007). The difference in their ability to cause the formation of stable carbon‐centered radicals within soy proteins may relate to the type of free radical they initially produce.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad peaks are typical of overlapping signals in polycrystalline or powdered samples. All of the reducing agents examined here have been shown to catalyze the oxidation of methionine and/or linoleic acid when added to ISP aqueous slurries (Boatright and Lu 2007; Lei and Boatright 2007). The difference in their ability to cause the formation of stable carbon‐centered radicals within soy proteins may relate to the type of free radical they initially produce.…”
Section: Resultsmentioning
confidence: 99%
“…Soy proteins are known to contain products of lipid oxidation, which produce volatile compounds responsible for the odor of soy protein products (Wolf and Cowan 1971; Sessa and Rackis 1977; Boatright and Lu 2007). More recently, products from the oxidation of sulfur‐containing amino acids have also been shown to contribute to the odor of soy protein products (Lei and Boatright 2007). Oxidation of lipids and amino acids is initiated by free radicals and results in chain reactions that produce additional free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been well documented that transition metals and heme proteins in muscle foods can catalyze protein and lipid oxidation responsible for the toughened texture, poor flavor, and/or unappealing odor of meats (Thanonkaew and others 2006). Furthermore, while studying the formation mechanism of methanethiol in ISP, we found that a transition metal ion cocktail containing Fe 3+ , Co 2+ , and Mn 2+ could effectively catalyze methanethiol formation from methionine in the presence of sulfite and oxygen (Lei and Boatright 2007). The major transition metals detected from ISP include iron (160 ppm), zinc (36 ppm), copper (14 ppm), manganese (11 ppm), and cobalt (< 5 ppm) (Perkins 1995).…”
Section: Resultsmentioning
confidence: 99%
“…Thermoplastic processing of BM requires the addition of excess sodium sulphite [19]. Sulphite ions are known to form sulphite and sulphate radical anions, where the sulphate radicals are capable of interacting with methionine in the presence of transition metal ions and oxygen to form methyl mercaptan [20,21]. Methyl mercaptan formation is thought to be initiated by sulphite radicals produced from the interaction of sulphite ions with free transition metal ions and oxygen.…”
Section: Sulphite Side-reactionsmentioning
confidence: 99%
“…anions. The sulphate radical anion has an oxidising power similar to that of the hydroxyl radical and may induce the formation of methyl mercaptan in a similar manner to the hydroxyl radical [21]. Sulphite ions and methionine alone do not react to form methyl mercaptan, but in the presence of transition metal ions the formation of methyl mercaptan occurs spontaneously [21].…”
Section: Sulphite Side-reactionsmentioning
confidence: 99%